Introductory overview: Recommendations for approaching scientific visualization with large environmental datasets. (September 2021) - Kelleher, Christa; Braswell, Anna
Abstract: Scientific visualizations are the foundation for communicating results and findings to a variety of audiences. As the creation of novel and large environmental datasets has grown, this has necessitated new schemes and recommendations for creating effective visualizations. In this overview, we review the foundations of scientific visualization and considerations for visualization of large datasets within the context of the four Vs of big data (volume, variety, veracity, and velocity). Using big datasets requires making decisions as to whether to aggregate or preserve details, approaches for grouping to enable comparisons, and considering how best to show complex data in many-dimensional space. To enable more effective visualizations, we provide several considerations regarding common decisions faced during the visualization process. These recommendations are accompanied by examples applied to existing large datasets. While our recommendations are just that, they encourage intentionality and awareness of the choices faced when visualizing scientific datasets. Highlights: We discuss the challenges of visualizing large environmental datasets. We outline choices faced when creating scientific visualizations for datasets with large volume or variety. We present approaches for approaching and improving large volume or multi-dimensional visualizations. We provide several examples using publicly available datasets and open code.